Exploring the backgrounds and shaping of beginning student teachers in Ghana: toward greater contextualisation of teacher education - Akyeampong, Kwame; Stephens, David (International Journal of Educational Development, 2002)
Teacher education programmes are often quite similar in their framework and content but often lack sufficient reflection on the personal background and the socio-political forces that shape teachers’ roles and identity within the systems in which they operate. This paper explores this issue by using Ghana as a case study and discusses implications for its teacher education programmes and policies. Key characteristics of beginning student teachers found were: weak qualifying grades in two fundamental school subjects, mathematics and English, a waiting period of 2–5 years prior to entering teachers’ college, and apparently sharp differentials in trainees’ socio-economic background as compared to typical Ghanaian communities. They come to training with rich and varied images of teachers, teaching and the profession, but, in addition, many beginning trainees also express little desire to teach at primary school level, mainly for reasons of status and insufficient fringe benefits. These factors, we argue, should be taken into more account in the design of college programmes and the development of teacher education policies. The paper concludes with a call to teacher education systems, especially in Africa, to look more closely at, and learn from, who comes for training, what they bring with them, and how they perceive themselves in relation to teaching, training and future aspirations.
Keywords: Beginning student teachers; Ghana; Teacher education; Teacher identity; Teacher images

The Ghana ICT for Accelerated Development (ICT4AD) Policy - Republic of Ghana (2003)
ghana ict for accelerated development policy
Keywords: ⛔ No INSPIRE recid found

Ghana Education Act, 2008 - Parliament of the Republic of Ghana (2008)

The Ghana ICT for Accelerated Development Policy - The Republic of Ghana (2003)

The importance of posting and interaction with the education bureaucracy in becoming a teacher in Ghana - Hedges, John (International Journal of Educational Development, 2002)
This paper addresses some of the issues surrounding the posting of newly trained teachers in Ghana. It specifically investigates the assertion that the posting system is ‘ineffective’ from the perspective of newly trained teachers who have been through the process. It emerged from analysis of the qualitative data that newly trained teachers’ experiences and perceptions of the posting process had a significant impact on their occupational culture. The research draws upon documents, interviews with members of the education bureaucracy, and interviews with 23 newly trained teachers posted to basic schools in rural areas in Central Region. The paper illuminates some of the problems involved in posting newly trained teachers to rural schools and looks for explanations as to why some teachers take up their postings and others do not.
Keywords: Basic education; C:Ghana; Deployment; Ghana; Induction; NQTs; Teacher education

An Evaluative Study of a Distance Teacher Education Program in a University in Ghana - Sampong, Kwasi Addo (The International Review of Research in Open and Distributed Learning, 2009)
The study used an adaptation of Provus’ discrepancy evaluation model to evaluate a distance teacher education program in the University of Cape Coast, the premier teacher education institution in Ghana. The study involved comparing performance data of the program as perceived by students and faculty/administrators to standards prepared from the program’s design. Performance data was obtained by administering two survey instruments to a random sample of students and faculty/administrators. Discrepancies between performance and standards were reported. The study concluded that although there were some discrepancies between program standards and performance the program is fulfilling its purpose of upgrading the professional and academic performance of a large number of teachers in the public K-8 schools in Ghana.

Open and distance learning (ODL) teacher education to support teacher development in Ghana: an evaluation report - Akyeampong, Kwame; Mensa, D; Abu-Yeboah (Ghana Education Service, 2007)

Education Strategic Plan 2003-2015 - Ministry of Education, Ghana (Government of Ghana, 2003)

Educational reform in Ghana: the leadership challenge - Zame, Martin Y.; Hope, Warren C.; Respress, Trinetia (International Journal of Educational Management, 2008)

Access to Basic Education in Ghana: The Evidence and the Issues. Country Analytic Report. - Akyeampong, Kwame; Djangmah, Jerome; Oduro, Abena; Seidu, Alhassan; Hunt, Frances (ERIC, 2007)

Education Strategic Plan 2003–2015 - Ministry of Education, Ghana (2003)

An Investigation of Provision of Quality Basic Education in Ghana: A Case Study of Selected Schools in the Central Region - Ampiah, Joseph (Journal of International Cooperation in Education, 2008)
Keywords: ⛔ No DOI found

The Views of Educational Practitioners in Ghana on ICT Use and Instructional Design Practice for Promoting Quality Education - Sarfo, Frederick Kwaku (Seventh IEEE International Conference on Advanced Learning Technologies (ICALT 2007), 2007)
Many ICT boosters are of the view that ICT on its own can promote quality teaching and learning. In line with this metaphor, the need to provide computers in the classrooms often takes precedence over training teachers to acquire skills in instructional design. However, it is evident in the instructional technology literature that good design of the learning task by the teacher is the fundamental requirement for quality teaching. This study was intended to explore the views of 90 educational practitioners (students, teachers and policy makers) in Ghana on the use of ICT and good design of instruction by the teacher for quality teaching and learning. Five Point Likert-type scales were used for the data collection. The results of the study indicate that in Ghana students are not very certain as to whether ICT or teachers can facilitate the implementation of the first five principles of instruction for quality teaching and learning. Moreover, a great number of teachers and policy makers are of the view that teachers can facilitate the implementation of the first five principles of instruction better than an ICT. However, it was recommended by the students, teachers and policy makers that both teachers and students should be trained to use ICT to facilitate teaching and learning.

Project overseas: Teachers helping teachers - Anonymous (Alberta Teachers Association, 2007)
Ghana: Celebrating 50 years of independence

The Ghana ICT for Accelerated Development Policy - Ministry of Communications (2003)

Abolishing School Fees in Africa: Lessons Learned in Ethiopia, Ghana, Kenya and Mozambique - Birger, Fredriksen; Craissati, Di (The World Bank, 2009)

A guide to developing the ICT curriculum for early childhood education. - Siraj-Blatchford, I; Siraj-Blatchford, J (Stylus Publishing, LLC., 2006)